2018
DOI: 10.3390/geosciences8030081
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Performance of Six Drought Indices in Characterizing Historical Drought for the Upper Blue Nile Basin, Ethiopia

Abstract: The Upper Blue Nile (UBN) basin is less-explored in terms of drought studies as compared to other parts of Ethiopia and lacks a basin-specific drought monitoring system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
71
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(88 citation statements)
references
References 41 publications
4
71
0
1
Order By: Relevance
“…Additionally, among the rainfall-based drought indices, the SPI9 had the lowest percentage of months with drought events compared with the SPI3 and SPI6. This is in line with other studies [46], where the author found that agricultural-based drought indicators depict relatively larger values of drought months compared with the meteorological drought indices. The maximum drought duration varied among the different drought indicators.…”
Section: Comparison Of Drought Characteristicssupporting
confidence: 92%
See 2 more Smart Citations
“…Additionally, among the rainfall-based drought indices, the SPI9 had the lowest percentage of months with drought events compared with the SPI3 and SPI6. This is in line with other studies [46], where the author found that agricultural-based drought indicators depict relatively larger values of drought months compared with the meteorological drought indices. The maximum drought duration varied among the different drought indicators.…”
Section: Comparison Of Drought Characteristicssupporting
confidence: 92%
“…Based on our analysis, the maximum drought duration appeared to be higher in the meteorological-based indices than the agricultural-based indices. This is primarily because the meteorological-based drought indices integrate the drought condition over a longer period of time than do the agricultural-based drought indices [46]. The drought intensity was found to be higher in the agricultural-based drought variables and lower in the metrological-based drought indices.…”
Section: Comparison Of Drought Characteristicsmentioning
confidence: 95%
See 1 more Smart Citation
“…In 2015-2016, another drought event associated with El Niño affected EA, with 24 million people facing critical and emergency food insecurity by August 2016. Drought indices have recently been used to characterize historical episodes in the Upper Blue Nile Basin in Ethiopia [8] and intraseasonal descriptors of wet and dry spells were applied to equatorial EA using rain gauge data [9]. Excessive rainfall was recorded during late 2015 and the March-May 2016 rainy season, leading to flooding in parts of Somalia, Kenya, Ethiopia, and Uganda (source: United Nation Office for the Coordination of Humanitarian Affairs, UN OCHA, http://www.unocha.org, last accessed 13 March 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In many parts of the world, the coverage of this information is not known or properly documentend because of data scarcity. As a result, many drought analysis studies, especially in sub-Saharan Africa, have been using point data, particularly observed rainfall datasets [4,5]. This has been causing inadequate information about drought coverage, thus affecting the livelihood of many people in this region.…”
Section: Introductionmentioning
confidence: 99%